Ungrading: Socially Just Assessment Practices for the PA Classroom - Jeannine Love; Jamie Levine Daniel (Journal of Social Equity and Public Administration)
Advancing social justice through public service requires administrators to cultivate particular capacities. To meet this need, public affairs programs and instructors are developing curricula that: incorporate content regarding systemic inequities; examine sociohistorical contexts in which such inequities are created and perpetuated; and, illuminate power dynamics embedded within these systems by utilizing concepts grounded in critical theory. However, engaging in social justice work requires administrators to not only assess existing power relations but also actively transform them. Thus, public administration curricula must also incorporate capacity building for participatory democracy. Students need opportunities to experience transformative processes with supportive guidance. This article examines ungrading as one tool instructors can employ to actively shift power dynamics, model participatory public engagement for future practice, and enhance deeper and more equitable student learning in the process.